GEOCHRONOLOGY OF TRIASSIC-JURASSIC GRANITOIDS IN THE SOUTHERN FRAMING OF THE MONGOL-OKHOTSK FOLDBELT AND THE PROBLEM OF EARLY MESOZOIC GRANITE FORMATION IN CENTRAL AND EASTERN ASIA - Sorokin A.A.; Sorokin A.P.; Yarmolyuk V.V.; Kotov A.B.; Kudryashov N.M.; Jinyi L. (My University, 2004)
Early Mesozoic geological events played an important role in the structural evolution of Eastern and Central Asia. They involved collision between Siberia and Sino-Korean continents. This was accompanied by the closure of the Solonker paleocean in Early Triassic and Mongol-Okhotsk paleocean no later than in Middle Jurassic, and formation of a convergent boundary along the Pacific margin. These events generated largescale granitoid magmatism. However, existing concepts of the relation between tectonic and magmatic processes in the evolution of the considered region are not always supported by geological and geochronological data. Our paper presents geochronological data on granitoids from northeastern margins of the Argun and Bereya-Jiamusi terranes. These data make it possible to significantly refine the scale of Early Mesozoic magmatism in the southern framing of the Mongol-Okhotsk foldbelt and correlate it with other regions of Eastern and Central Asia.
Keywords: Jurassic; Triassic; Mesozoic::Jurassic; Mesozoic::Triassic; Мезозой::Триасовая; Мезозой::Юрская